2004
DOI: 10.1205/cerd.82.11.1438.52028
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of CaCO3 Nanoparticles by Carbonation of Lime Solutions in Reverse Micellar Systems

Abstract: Synthesis of CaCO3 nanoparticles by carbonation of lime solutions in reverse micellar systems Heeres, Hero; Jain, R.; Mehra, A.; Dagaonkar, M.V. pplication of reverse micelles for the synthesis of nano-sized calcium carbonate particles in different solvents (cyclohexane, decane and heptane) has been investigated. The effect of the mole ratio of water-to-surfactant (R) and type of solvent has been studied on the size and nature of the carbonate particles. The results indicate that an increase in water-to-surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Giasson et al examined an overbased calcium sulfonate dispersion showing an average calcium carbonate core radius of 2.0 nm with a standard deviation of 0.4 nm by using SAXS [40]. Dagaonkar et al [41] investigated the influence of amount of water and dispersive media on the CaCO 3 nanoparticle size mediated by the surfactant 1,2-bis-(2-ethylhexyl-oxycarbonyl)-1-ethane sulfonate (AOT), colloid particles of diameter ranged from 25 nm to around 200 nm were produced mainly depending on the volume of water added.…”
Section: Light Scattering Measurements (Dls and Sls) And Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Giasson et al examined an overbased calcium sulfonate dispersion showing an average calcium carbonate core radius of 2.0 nm with a standard deviation of 0.4 nm by using SAXS [40]. Dagaonkar et al [41] investigated the influence of amount of water and dispersive media on the CaCO 3 nanoparticle size mediated by the surfactant 1,2-bis-(2-ethylhexyl-oxycarbonyl)-1-ethane sulfonate (AOT), colloid particles of diameter ranged from 25 nm to around 200 nm were produced mainly depending on the volume of water added.…”
Section: Light Scattering Measurements (Dls and Sls) And Transmissionmentioning
confidence: 99%
“…The work of Kandori et al [14] and Roman et al [11] demonstrated that the microemulsion size thus the produced CaCO 3 particles increased with addition of water by light scattering characterization. Dagaonkar et al [41] and Sugih et al [54] found that high water-to-surfactant molar ratios led to the formation of larger nanoparticles in gas-reverse micellar systems through direct electron microscopy observation. Mann's group discovered the water-induced mesoscale phase transformation and morphologies change upon variant water-to-calcium carbonate ratio [46].…”
Section: Alkaline Calcium Saltmentioning
confidence: 99%
“…CaCO3 nanoparticles attract attention, due to their wide range application coating, plastic industry, paper, drug delivery, etc.CaCO3 nanoparticles have been produced using several methods; carbonization [1][2][3][4][5][6][7][8][9], tubular reactor [10], microemlusion [11][12][13][14][15], mechanochemical reaction by mechanical milling of CaCl2+ Na2CO3 powder mixture [16] and milling of calcite in presence of additive [17].…”
Section: Introductionmentioning
confidence: 99%
“…13 There are many types of nanoparticles synthesised via this method such as metal nanoparticles (Pt, Rh, Pd, and Ir), metal oxide nanoparticles, and other Inorganic nanoparticles (CdS and CaCO 3 ). 14,15 O'Hare et al reported the first synthesis of a layered double hydroxide (LDH) using this approach. 16,17 In the present study, we report the synthesis of nanosized calcium aluminium LDHs in dodecylsulfate reverse micelles.…”
Section: Introductionmentioning
confidence: 99%